Technology in Feeding Management to Increase Ruminant Productivity - Budi Haryanto (Indonesian Center for Animal Research and Development, 2015)
Traditional feeding management in ruminants is defined by allowing the animal to find their own feed, consisted of raw materials of grasses and leguminous foliages as much as possible (ad libitum) to get a high productivity; however, it needs longer period of time to reach maximum level of production. An advanced feeding management of ruminant is defined as: (1) Processing feed ingredients to improve the nutritive value; (2) Supplementing the animal with substances into the dietary formula to manipulate the rumen ecosystem either by reducing the protozoa population, increasing the concentration of certain nutrients, changing the rumen characteristics; and (3) Changing the site of digestion of the nutrients to increase the absorption and feed utilization. Many research works have been carried out to evaluate the effects of process technology on the efficiency of feed utilization. Improving feeding management will increase livestock production.